2014
DOI: 10.1002/cam4.314
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epidermal growth factor signaling by the cardiac glycoside ouabain in medulloblastoma

Abstract: Epidermal growth factor (EGF) signaling regulates cell growth, proliferation, and differentiation. Upon receptor binding, EGF triggers cascades of downstream signaling, including the MAPK and phosphoinositide-3-kinase (PI3K)/Akt signaling pathways. Aberrant expression/activation of EGFR is found in multiple human cancers, including medulloblastoma, the most prevalent pediatric brain cancer, and often has been associated with metastasis, poor prognosis, and resistance to chemotherapy. Na,K-ATPase is an ion pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
(81 reference statements)
2
20
0
Order By: Relevance
“…ATP1A1 is the catalytic subunit of Na + ,K + -ATPase, an ion pump that also plays a role in signal transduction when inhibited by ouabain (Reinhard et al, 2013), making it a candidate therapeutic target for diseases such as medulloblastoma (Wolle et al, 2014). MAPK1 26, 2017; phosphorylates ATP1A1 in response to insulin (Al-Khalili et al, 2004) and proinsulinconnecting peptide (C-peptide) (Zhong et al, 2004) stimulation, potentially on T81.…”
Section: Role Of Novel Tested Egfr Pathway Edgesmentioning
confidence: 99%
“…ATP1A1 is the catalytic subunit of Na + ,K + -ATPase, an ion pump that also plays a role in signal transduction when inhibited by ouabain (Reinhard et al, 2013), making it a candidate therapeutic target for diseases such as medulloblastoma (Wolle et al, 2014). MAPK1 26, 2017; phosphorylates ATP1A1 in response to insulin (Al-Khalili et al, 2004) and proinsulinconnecting peptide (C-peptide) (Zhong et al, 2004) stimulation, potentially on T81.…”
Section: Role Of Novel Tested Egfr Pathway Edgesmentioning
confidence: 99%
“…found that treatment of digoxin through the inhibition of hypoxia‐inducible factor (HIF)1 α inhibited mesenchymal transition and invasion in glioblastoma SNB75 and U87 cells. Wolle et al . reported that ouabain did not transactivate EGFR but inhibited its effect via promotion of the activation of PI3K/Akt and ERK1/2 in medulloblastoma cells.…”
Section: Preclinical Evidence and Potential Mechanisms For Na+/k+‐atpmentioning
confidence: 99%
“…For example, the overexpression of voltage gated K + channels was observed in breast-, colon-and prostate cancer and medullablastoma (11,12) and their inhibition attenuates neuroblastoma and endothelial cell migration (13,14). Consistently, the Na + /K + -ATPase inhibitor ouabain (also known as g-strophanthin) attenuates medullablastoma cell migration and the localisation of Tyr397-phosphorylated FAK to lammelipodia (15). Furthermore, the voltage gated K + v1.2 channel induces directional migration of mesenchymal bone marrow or CHO cells through phosphorylation of Tyr397-FAK (16) as well as wound healing in an animal model (17).…”
Section: Fenofibrate Inhibits Tumour Intravasation By Several Indepenmentioning
confidence: 90%